Trade Globalization and Its Impact on Welfare in Indonesia - Yulinda Nurul Aini; Purba, Yanti Astrelina; Meilianna, Ruth (RMPI-BRIN, 2018)
Indonesia was experiencing trade globalization in the form of decreasing and uniforming tariffs and eliminating various non-tariff barriers. Trade globalization had a positive and negative impacts on Indonesian’s welfare. Therefore, this study aims to analyze the effect of Trade’s Globalization on Indonesian’s Welfare. The Trade globalization was measured by three variables, namely Trade Openness, Inflation, and Exchange Rate. While Indonesian’s Welfare was measured by three aspects, namely education aspect using School Enrollment, health aspect using Life Expectancy, and economic aspect using the GDP Per capita. The data used was time series data from 1971-2016. This study applied mix-methods, quantitatively using Structural Equation Modeling Partial Least Square (SEM-PLS) and qualitatively using desk study. The results indicated that Trade Openness and Exchange Rate were positive and significant indicators in measuring Trade globalization. In addition, School Enrollment and GDP Per capita were also positive and significant indicators in measuring Indonesian’s Welfare. In general, the test showed that Trade globalization had a negative and significant influence on Indonesian’s Welfare. This fact suggested the importance of controlling exchange rate stability in Indonesia, because exchange rate could affect people’s ability to maintain lives through purchasing power. In addition, globalization measured through Trade Openness could be an accommodation to obtain new technology in various fields, such as in education to improve the quality of human resources, in health sector to treat various diseases and reduce the risk of death, and in economy sector to increase Per capita income.